1998
DOI: 10.1002/mawe.19980291008
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß von Sauerstoffzusätzen beim Gasnitrieren auf den strukturellen Aufbau von Nitrierschichten

Abstract: Die Wirkung kontrollierter sauerstoffhaltiger Zusltze beim Gasnitrieren von Stahlen auf den strukturellen Aufbau der Nitrierschichten und den Ablauf der Nitrierreaktion untcr technischen Bedingungen wurde mit metallkundlichen Untersuchungsmcthoden unter Einbeziehung der Miissbauer Spektroskopie verfolgt.Die Ergebnisse der durchgefuhrten Untersuchungen zeigen, daR Sauerstoffzusatze unterhalb der Oxidationsgrenze des reinen Eisens das Nitrierverhalten unlegierter Stlhle etwas verbessern konnen. Weiter konnte gez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The measured XRD reflections f peak (x) are a sum of physical and instrumental influences, which can be treated as a convolution given in (3). Line broadening in XRD arises mainly due to three factors: the machine influence, the strain broadening and the effects based on finite grains (size effect).…”
Section: Xrd Peak Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The measured XRD reflections f peak (x) are a sum of physical and instrumental influences, which can be treated as a convolution given in (3). Line broadening in XRD arises mainly due to three factors: the machine influence, the strain broadening and the effects based on finite grains (size effect).…”
Section: Xrd Peak Analysismentioning
confidence: 99%
“…As an example, plasma-and gas nitriding are established methods for surface treatment [2,3]. Alternatively, it is possible to treat the surface with laser radiation and to directly synthesize hard coatings [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The processes and the structure of the corrosion layers caused by nitridation can be derived from kinetic considerations and it is known from the experience with nitriding [13,14] and oxinitriding [15,16], Fig. 13 shows the layers formed by ingress of nitrogen, upon oxidation growth of the oxides Fe 3 O 4 and FeCr 2 O 4 should occur by outward diffusion of cations.…”
Section: Kineticsmentioning
confidence: 99%
“…The NH 3 -H 2 O is also oxidizing, and according to the experience from "gas oxinitriding" an oxide layer grows on the iron nitrides, which is porous so that nitrogen can penetrate [15,16]. It is reported that the nitridation rate is even enhanced in the presence of oxidizing gases H 2 O, CO 2 or air.…”
Section: Kineticsmentioning
confidence: 99%